Reflections on Islamisation and the Future of the Women’s Rights Movement in ‘Naya’ Pakistan - Sonia Awan (Angles)
This paper examines how the Islamisation of education is likely to impact the future of the women’s rights movement in Pakistan. Recently, the Pakistan Tehreek-e-Insaf (PTI, or party for social justice) government introduced the Single National Curriculum (SNC), a reform of the education system that enhances the volume of Islamic Studies and wherein Urdu, the national language, is promoted as a parallel medium of instruction. The central argument of this paper is that such developments are regressive and that they could prove detrimental to the women’s rights movement. Historically, the formation of the Women’s Action Forum (1981) and its rising against Zia’s Islamic dictatorship (1983) remains one of the most memorable moments of the women’s rights movement in contemporary Pakistan’s history. But in the decades that followed, the movement began sagging and stumbling. The recent Women’s Marches are evidence that deep ideological divisions running within the movement are impeding the achievement of tangible goals. This is a critical juncture because the implementation of an Islamic curriculum will set off the process of the bottom-up Islamisation of society. Gradually, when everything shall be sorted out ‘according to Islam and Islamic principles’, a large chunk of women’s demands will be simply chucked away as un-Islamic, thus inadmissible. Pakistani society will likely become less tolerant than it is already and the few freedoms that women still enjoy shall be taken away one after the other. This is a gloomy scenario, but it is avoidable. Now could be the time for the movement to focus on defining attainable goals and pushing for the achievement and consolidation of women’s human rights. While the Islamisation of education appears like a potential threat to the movement now, activists might as well make of it an element that reinvigorates the movement from the inside and gives it a new direction and sense of purpose.